PO 18118 - Epidemiological study of ankle fractures - Christovan Ribeiro, Evandro Junior; Damião Prata, Sérgio; Rizzo, Marco Antônio (Scientific Journal of the Foot & Ankle, 2019)
Introduction: Ankle fractures account for 10% of all fractures and rank second in frequency among lower limb fractures, behind only hip fractures. The lack of studies on the epidemiology of ankle fractures available in the Brazilian literature motivated a more in-depth study to better describe these fractures. The objective of this study was to analyze the epidemiological characteristics of ankle fractures. Methods: An epidemiological, prospective, descriptive, observational study of ankle fractures in a convenience sample taken from the study hospital. In total, 150 patients were evaluated from March 2016 to March 2017. A questionnaire was prepared to collect patient data and variables for subsequent analysis. The following parameters were analyzed: age, occupation, sex, ethnicity, marital status, education, emergency transport, time of trauma, day of the week of trauma, trauma mechanism, fracture type, affected limb, classification, treatment, associated injury and length of hospital stay. Results: Among the patients with ankle fractures, 33.66% of the fractures occurred in the afternoon. A total of 61.34% of the ankle fracture patients were men, and the right was the most commonly affected side. The mean age was 40.48 years. The most frequent trauma mechanism was fall from height, which accounted for 51.42% of fractures. Weber type B fractures were the most frequent type. Conclusion: Ankle fractures treated at the Department of Orthopedics and Traumatology during the study period primarily affected married, Caucasian patients aged between 40 and 50 years with up to a primary education level; fractures were most frequently on the right side and primarily occurred in the afternoon and on Sundays. Sprain due to fall from height was the most common trauma mechanism, and exposed fracture occurred in 28% of the cases.